(untitled) (Baghdad Science Journal, 2025)
Films of silver oxide of different thickness have been prepared by the chemical spray paralysis. Transmission and absorption spectra have recorded in order to study the effect of increasing thickness on some optical parameter such as reflectance, refractive index , and dielectric constant in its two parts . This study reveals that all these paramters affect by increasing the thickness .